Peroxynitrite-mediated modification of proteins at physiological carbon dioxide concentration: pH dependence of carbonyl formation, tyrosine nitration, and methionine oxidation - Tien, Ming (The National Academy of Sciences, 1999)
The ability of peroxynitrite to modify amino acid residues in glutamine synthetase (GS) and BSA is greatly influenced by pH and CO(2)(.) At physiological concentrations of CO(2) (1.3 mM), the generation of carbonyl groups (0.2–0.4 equivalents/subunit) is little affected by pH over the range of 7.2–9.0, but, in the absence of CO(2), carbonyl formation increases (from 0.1- 1.2 equivalents/subunit) as the pH is raised from 7.2 to 10.5. This increase is attributable, in part but not entirely, to the increase in peroxynitrite (PN) stability with increasing pH. Of several amino acid polymers tested, only those containing lysine residues yielded carbonyl derivatives. In contrast, the nitration of tyrosine residues of both GS and BSA at pH 7.5 almost completely depends on the presence of CO(2)(.) However, the pH profiles of tyrosine nitration in GS and BSA are not the same. With both proteins, nitration decreases ≈65% with increasing pH over the range of 7.2–8.4, but, then in the case of GS only, there is a 3.4-fold increase in the level of nitration over the range pH 8.4–8.8. The oxidation of methionine residues in both proteins and in the tripeptide Ala-Met-Ala was inhibited by CO(2) at both high and low pH values. These results emphasize the importance of controlling the pH and CO(2) concentrations in studies involving PN and indicate that PN is not likely to contribute appreciably to carbonyl formation or oxidation of methionine residues of proteins at physiological pH and CO(2) concentrations.